SACROILIAC ARTHROMYELITIS: CASE REPORT: ARTROMIELITIS SACROILIACA: REPORTE DE CASO - Sernaque Mechato, Roger Antonio (2024)
Infectious sacroiliitis is a rare condition that is sometimes diagnosed late due to the poor specificity of the symptoms. In addition, imaging techniques such as scintigraphy, tomography, and nuclear magnetic resonance are required to assess the extent and severity of the lesions. If early diagnosis and treatment are made, the clinical evolution is satisfactory and leaves no sequelae. Clinical case: the case of an 83-year-old female patient is presented, with a history of ischemic cerebrovascular disease, high blood pressure, type 2 diabetes mellitus and urinary tract infection, who presented with moderately intense colic-like abdominal pain, afebrile, and reported that at the time After getting up from his chair he felt weakness in his left side. On admission, hypertensive, febrile with T°: 38°C SatO2: 98% with FiO2: 0.4. On physical examination, there was edema in MMII with pitting (+), distended abdomen, pain in the right flank and left hemiparesis. To the laboratory: hemoglobin 14.8 g/dl, platelets 38,000 μl, leukocytes 18,000 μl. Keywords: septic arthritis, septic sacrolileitis  (source: MeSH – NLM)